2013
DOI: 10.1038/bmt.2013.128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of being overweight on outcomes of hematopoietic SCT: a meta-analysis

Abstract: The impact of being overweight on outcome after hematopoietic SCT (HSCT) is controversial. We performed meta-analyses to evaluate the impact of being overweight on acute graft-versus-host disease (aGVHD) risk and survival. Original data were obtained from MEDLINE, and studies that evaluated being overweight before transplantation in recipients as a risk factor for aGVHD or a prognostic factor for overall survival (OS) were extracted. Study-specific relative risks on the log scale comparing overweight with non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Obesity is also included as one of the comorbidities, and a score is assigned based on BMI > 35 kg/m 2 in adults or BMI for age of the 95 th percentile or higher in children. While the role of obesity as an independent risk factor on allogeneic transplant outcomes, such as GVHD, relapse, non-relapse mortality (NRM), and overall survival, has been previously explored by several groups, inconsistencies have been reported depending on the study population (12-24). Recently, plasma biomarkers predictive of GVHD and NRM have been identified (25-27).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also included as one of the comorbidities, and a score is assigned based on BMI > 35 kg/m 2 in adults or BMI for age of the 95 th percentile or higher in children. While the role of obesity as an independent risk factor on allogeneic transplant outcomes, such as GVHD, relapse, non-relapse mortality (NRM), and overall survival, has been previously explored by several groups, inconsistencies have been reported depending on the study population (12-24). Recently, plasma biomarkers predictive of GVHD and NRM have been identified (25-27).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we expect that more candidates of HSCT will have these nutritional problems, which may increase the risk of morbidity and mortality after HSCT. In terms of body weight, several retrospective studies have shown the impact of pretransplantation body mass index (BMI) on the clinical outcome after allogeneic HSCT [8][9][10][11][12][13][14][15][16]. The results varied, but there is a clear trend of high BMI being associated with an increased risk of graft-versushost disease (GVHD) and nonrelapse mortality (NRM) and low BMI being associated with inferior overall survival because of an increased risk of relapse and NRM.…”
Section: Pretransplantation Assessment and Interventionmentioning
confidence: 99%
“…Overweight patients had the highest NRM but no inferior OS than normal-weight patients. Were the meta-analysis by Nakao et al, 13 the present study data and those from Fuji et al 14 pooled today, overweight would very likely no longer be associated with worse survival. However, Fuji et al 14 did identify underweight as a prognostic factor for poor OS because of an increased risk of relapse.…”
mentioning
confidence: 92%
“…13 The overweight group was protected from relapse. However, this benefit was offset by excessive NRM, leading to this study's major finding, namely that overweight demonstrate no difference in impact on OS compared with normal-weight patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation